LINE‐ and Alu‐containing genomic instability hotspot at 16q24.1 associated with recurrent and nonrecurrent CNV deletions causative for ACDMPV. Issue 12 (22nd August 2018) - Szafranski, Przemyslaw; Kośmider, Ewelina; Liu, Qian; Karolak, Justyna A.; Currie, Lauren; Parkash, Sandhya; Kahler, Stephen G.; Roeder, Elizabeth; Littlejohn, Rebecca O.; DeNapoli, Thomas S.; Shardonofsky, Felix R.; Henderson, Cody; et al.
Abstract: Transposable elements modify human genome by inserting into new loci or by mediating homology‐, microhomology‐, or homeology‐driven DNA recombination or repair, resulting in genomic structural variation. Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a rare lethal neonatal developmental lung disorder caused by point mutations or copy‐number variant (CNV) deletions of FOXF1 or its distant tissue‐specific enhancer. Eighty‐five percent of 45 ACDMPV‐causative CNV deletions, of which junctions have been sequenced, had at least one of their two breakpoints located in a retrotransposon, with more than half of them being Alu elements. We describe a novel ∼35 kb‐large genomic instability hotspot at 16q24.1, involving two evolutionarily young LINE‐1 (L1) elements, L1PA2 and L1PA3, flanking Alu Y, two Alu Sx, Alu Sx1, and Alu Jr elements. The occurrence of L1s at this location coincided with the branching out of the Homo ‐ Pan ‐ Gorilla clade, and was preceded by the insertion of Alu Sx, Alu Sx1, and Alu Jr. Our data show that, in addition to mediating recurrent CNVs, L1 and Alu retrotransposons can predispose the human genome to formation of variably sized CNVs, both of clinical and evolutionary relevance. Nonetheless, epigenetic or other genomic features of this locus might also contribute to its increased instability. Abstract : We describe a novel genomic instability hotspot at 16q24.1, including two L1 elements flanking five Alus, involved in formation of copy‐number variant (CNV) deletions causative for ACDMPV. Our data show that some evolutionarily young L1 and Alu retrotransposons can predispose the human genome to formation of both recurrent and variably‐sized CNVs of clinical and evolutionary relevance.